2009
DOI: 10.1242/jeb.030726
|View full text |Cite
|
Sign up to set email alerts
|

The effects of testosterone on immune function in quail selected for divergent plasma corticosterone response

Abstract: SUMMARYThe immunocompetence handicap hypothesis (ICHH) suggests that the male sex hormone testosterone has a dual effect; it controls the development and expression of male sexually selected signals, and it suppresses the immune system. Therefore only high quality males are able to fully express secondary sexual traits because only they can tolerate the immunosuppressive qualities of testosterone. A modified version of the ICHH suggests that testosterone causes immunosuppression indirectly by increasing the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 85 publications
(121 reference statements)
3
32
0
Order By: Relevance
“…Our results were more consistent with the interaction demonstrated by Roberts et al [31], than with covariance of T and C [25]. We argue that the mechanisms by which the two hormones interact cannot simply be attributed to their covariance, and that an SL-ICHH must account for complexity in interactions between sex-and stress-hormones [25,31,32]. Evans [34] argues that the effects of T and C on behaviour will be species-and context-dependent.…”
Section: Discussionsupporting
confidence: 88%
“…Our results were more consistent with the interaction demonstrated by Roberts et al [31], than with covariance of T and C [25]. We argue that the mechanisms by which the two hormones interact cannot simply be attributed to their covariance, and that an SL-ICHH must account for complexity in interactions between sex-and stress-hormones [25,31,32]. Evans [34] argues that the effects of T and C on behaviour will be species-and context-dependent.…”
Section: Discussionsupporting
confidence: 88%
“…Because GnRH is a releasing hormone that signals a cascade of hormones involved in reproduction, the immunosuppressive eVects detected may have been due to other hormones. For example, elevated testosterone can also result in increased levels of corticosterone (Casto et al 2001;Ketterson et al 1991;Klukowski et al 1997;Schoech et al 1999), which may directly suppress immune function (Roberts et al 2009). Similarly, the aromatization of testosterone to estradiol could be the cause of the immunosuppression observed here (Leitner et al 1996;Owen-Ashley et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, experimental increases in testosterone, within normal physiological limits, suppress immune function and increase parasite loads in several species (24,25). In addition, some studies in wild vertebrates have found that highranking males have high testosterone and/or glucocorticoids and poor health (18,21,26,27). Hence, in addition to the social stress associated with low rank, differences in reproductive effort also may cause status-related differences in health.…”
mentioning
confidence: 94%